2011
DOI: 10.4028/www.scientific.net/msf.679-680.595
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mobility Limiting Mechanisms in (0001) 4H and 6H-SiC MOSFETs

Abstract: To study the mobility limiting mechanisms in (0001) 4H-SiC and 6H-SiC MOSFETs, physics based modeling of the inversion mobility of has been done. Two very different limiting mechanisms have been found for 4H-SiC and 6H-SiC MOSFETs. The mobility in 6H-SiC MOSFETs is limited by phonon scattering while the 4H-SiC MOSFET mobility is limited by Coulombic at low electric fields and surface roughness scattering at high electric fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…As the value of μ FE is affected by carrier trapping at the MOS interface, the Hall effect mobility in the inversion layer (μ Hall ) has been extensively studied using Hall effect measurements. [5][6][7][8][9][10][11][12][13][14][15] This is because μ Hall can be evaluated, irrespective of the carrier trapping at the MOS interface, in contrast to μ FE . Hall effect measurements enable the simultaneous evaluation of the surface carrier density (N S ) and μ Hall of MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…As the value of μ FE is affected by carrier trapping at the MOS interface, the Hall effect mobility in the inversion layer (μ Hall ) has been extensively studied using Hall effect measurements. [5][6][7][8][9][10][11][12][13][14][15] This is because μ Hall can be evaluated, irrespective of the carrier trapping at the MOS interface, in contrast to μ FE . Hall effect measurements enable the simultaneous evaluation of the surface carrier density (N S ) and μ Hall of MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…28 Recently, we have observed that Al-implanted lateral MOSFETs processed without a protection during postimplantation annealing show a higher channel mobility 0021-8979/2012/112(8)/084501/6/$30.00 V C 2012 American Institute of Physics 112, 084501-1 (40 cm 2 V À1 s À1 ) with respect to devices fabricated using a protecting carbon capping layer (24 cm 2 V À1 s À1 ). 29 Although Coulomb scattering was recently indicated as the dominant factor which limits the channel mobility in 4H-SiC, 29,30 the impact of the morphological surface conditions on MOSFETs performances remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…27) The optical phonon scattering has been taken into account for the bulk mobility of SiC, and reported to have great impact on the total mobility. 28) Therefore, instead of acoustic phonon scattering mobility in conventional mobility models, [29][30][31][32][33] μ OP was applied to the improved mobility model with Coulomb scattering mobility (μ C ) 32) and surface roughness scattering mobility (μ SR ) 32) as follows:…”
Section: Experimental Methodsmentioning
confidence: 99%